Case management system (CMS): an evaluation among users - Nadianauli, Yaakub (2018)
Investments made in a new information system can help employees to improve their daily task and increase productivity. It can also lead to disastrous result if not managed well. Inland Revenue Board of Malaysia (IRBM) has invested in developing Case Management System (CMS) to help the auditors in managing their audit case files and reports online. CMS is a mandatory system that the auditors needed to use even though they have some reservations about it. This study, therefore, aimed to assess the success factors of CMS in IRBM from the auditors or the individual users‟ point of view. The DeLone and McLean Information System Success Model (D&M ISSM) was used to determine the relationship between its six constructs, namely, system quality, service quality, information quality, use, user satisfaction, and net benefit. Three hundred and thirty-eight (338) questionnaires were distributed online, and 105 responded. The respondents were officers from the desk audit, field audit, profiling, Monthly Tax Deduction (PCB) audit and investigation branches. The results indicated that only information quality influenced system use. System quality and service quality were, however, not significant. In addition to that, service quality and use influenced user satisfaction. Use and user satisfaction were also found to positively influence net benefit of CMS. The findings show that the auditors of IRBM care more in the quality of information provided by CMS and the service quality received from the CMS Help-Desk. Hence, IRBM should pay more attention to enhance features, such as information quality and service quality, when upgrading or developing a system that is mandatory for the users or has similar features as CMS. Extra attention to both features will help the system to attain success as described by the net benefits of CMS.